2021
DOI: 10.1002/alz.12305
|View full text |Cite
|
Sign up to set email alerts
|

Plasma hydrogen sulfide: A biomarker of Alzheimer's disease and related dementias

Abstract: While heart disease remains a common cause of mortality, cerebrovascular disease also increases with age, and has been implicated in Alzheimer's disease and related dementias (ADRD). We have described hydrogen sulfide (H2S), a signaling molecule important in vascular homeostasis, as a biomarker of cardiovascular disease. We hypothesize that plasma H2S and its metabolites also relate to vascular and cognitive dysfunction in ADRD. We used analytical biochemical methods to measure plasma H2S metabolites and MRI t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Despite the growing interest in H 2 S as an endogenous gaseous mediator that influences human health, aging, and susceptibility to numerous diseases [ 8 , 17 , 34 , 35 ], research has been limited by the lack of a quantitative stable isotope dilution LC-MS/MS method for the analyte. Moreover, the relative contributions of host versus enteric gut microbial sources for H 2 S production in humans are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing interest in H 2 S as an endogenous gaseous mediator that influences human health, aging, and susceptibility to numerous diseases [ 8 , 17 , 34 , 35 ], research has been limited by the lack of a quantitative stable isotope dilution LC-MS/MS method for the analyte. Moreover, the relative contributions of host versus enteric gut microbial sources for H 2 S production in humans are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have noted dramatic effects of H 2 S on mitochondrial respiration, tissue preservation, hibernation, circadian rhythm, metabolism, and related functions [ [12] , [13] , [14] ]. Human studies have reported clinical associations between H 2 S and aging [ 8 , 9 ], cardiovascular disease [ 15 , 16 ], and other degenerative diseases [ 17 ]. These studies typically measure H 2 S by assessing sulfide concentration without internal standards, or H 2 S production capacity by incubating the sample after collection [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported previously that plasma level of free H 2 S tends to be decreased in AD patients (34 μM vs. 45 μM in controls) [ 130 ], while another study published recently has not confirmed this suggestion. The latter study showed no differences in the free plasma H 2 S level in AD patients compared with the plasma of control individuals; however, disturbances in the total sulfide (acid-labile and bound) have been found by these authors in the AD patients [ 131 ]. Amyothrophic lateral sclerosis (ALS) is a neurodegenerative disease causing a selective degeneration of upper and lower motor neurons.…”
Section: Reactive Sulfur Species In Diseasesmentioning
confidence: 99%
“…Rarely, the higher level of 130–150 µM was reported. Surprisingly, some authors presented that the level of free H 2 S in healthy human plasma was as low as >1 µM or less [ 131 , 144 ]. The reason of such a big discrepancy of the reported values is the fact that various methods were used to evaluate the amount of H 2 S. The most commonly used methods include colorimetric method based on the methylene blue formation, fluorometric assays using different fluorescence dyes (e.g.…”
Section: Reactive Sulfur Species In Diseasesmentioning
confidence: 99%
“…Such a clinical response is likely due to the involvement of different pathways, and this broadly reflects the pleiotropic activity of H 2 S. Whether target pathways work independently of each other is not yet clear, but the biology of H2S promises future development of tools at several levels. Some clinical application as biomarker has been published in cardiovascular and renal risk, 3,4 cognitive impairment 5 and blood pressure monitoring. 6 The secondary prevention of ischaemia/reperfusion injury is another promising field for H 2 S in both myocardial and cerebral flow 7,8 and sepsis as well.…”
Section: E D I T O R I a Lmentioning
confidence: 99%